Constructing polymeric proton donor and proton acceptor in layer-by-layer structure for efficient proton transfer in PEMFC. (2nd March 2016) - Meemuk, Chalanda; Chirachanchai, Suwabun
Abstract: Heterocyclic compounds are known as proton transfer species for anhydrous polymer electrolyte membrane (PEM), for which efficient proton conductivity at high operating temperature has yet to be found. The present work proposes an approach to enhance the proton transfer of the membrane by combining the concept of proton donor and acceptor with an ordered structure, i.e. layer-by-layer (LbL). By simply applying poly(acrylic acid) (PAA) as a polymeric proton donor and benzimidazole (BIm) conjugated on branching poly(ethyleneimine) as a polymeric proton acceptor and alternately coating the sulfonated poly(ether ether ketone) (SPEEK), a LbL membrane can be obtained. The proton transfer can be fine-tuned by the number of bilayers, and at that time, the 20-bilayered SPEEK/BIm-PEI/PAA is an optimal condition, which achieves a balance between the hydrogen bond and chain mobility under LbL packing that allows a 1.5 higher order of magnitude conductivity than an as-prepared SPEEK membrane even at a high operating temperature range (90–170 °C). The present work, for the first time, shows how a simple LbL technique is practical for constructing high-ordered structure of proton donor and acceptor species on the membrane surface for the efficient proton transfer in a PEM. Highlights: The layer-by-layer membranes of proton donor and accepter improve proton conductivity in PEMFC. Balance of hydrogen bond network and mobility among proton transfer species is a key factor for proton conduction trough LbL SPEEKPEM. The layer-by-layer membranes containing heterocyclic functional group can maintain high proton conductivity in high operating temperature.